The practice, the horizon, and the chain - Samatar, Sofia (Tor, 2024)
The boy was raised as one of the Chained, condemned to toil in the bowels of a mining ship out among the stars. His whole world changes--literally--when he is yanked "upstairs" and informed he has been given an opportunity to be educated at the ship's university alongside the elite. Overwhelmed and alone, the boy forms a bond with the woman he comes to know as "the professor," a weary idealist and descendent of the Chained who has spent her career striving for validation from her more senior colleagues, only to fall short at every turn. Together, the boy and the woman will embark on a transformative journey to grasp the design of the chains that fetter them both--and are the key to breaking free. --